Procedimentos para especificação e compra de materiais da construção civil de menor impacto ambiental - Flores, Carina Zamberlan (2011)
The construction industry is responsible for various environmental impacts from the extraction of nonrenewable resources, emission of greenhouse gases till the final disposition of waste. Materials are a significant part of the building, thus, their right choice contributes to the sustainability of the building as a whole. The lack of technical information, manufactures transparency and accessible environmental assessment methodologies hampers the work of professionals who do not know how to contribute positively to this scenario. This situation is aggravated by the lack of a Brazilian database to identify the main environmental impacts of construction materials based on life cycle analysis. This research aims to propose a procedure for analysis and subsequent selection, specification and purchase of environmental preferable construction materials. To achieve this propose, it was performed a bibliographic review about the specification of sustainable materials and critical analysis of some environmental assessment methodologies of products, checking common points, organization, categories, criteria, certificated materials and other specific factors that allow to compare information. Also, an interview with architects and civil engineers of the State of Parana was conducted, which evaluated key questions, problems and actions of these professionals on the subject. Thus, it was possible to perceive the lack of technical information on the subject by the manufacturer, lack of customer interest in accepting these new materials, availability of materials in some regions of the State and even ignorance of the professional about certifications, methodologies and guidelines for the choice of more sustainable materials. From the analysis of this information, it was proposed a procedure for the specification of environmental preferable construction materials, which is divided between design and construction steps. The first step aims to help the professional to select and specify materials in design. The construction step helps to evaluate the manufacturers as the material environmental performance is directly involved with the manufacturing process. The consequence of adopting this system will be the creation of a material database with public access. At the end of this procedure will be possible the creation of a material database where may occur information exchanges.